2021
DOI: 10.1155/2021/1090698
|View full text |Cite|
|
Sign up to set email alerts
|

The lncRNA Signatures of Genome Instability to Predict Survival in Patients with Renal Cancer

Abstract: Long noncoding RNAs (lncRNAs) exert an increasingly important effect on genome instability and the prognosis of cancer patients. The present research established a computational framework originating from the mutation assumption combining lncRNA expression profile and somatic mutation profile in the genome of renal cancer to assess the effect of lncRNAs on the gene instability of renal cancer. A total of 45 differentially expressed lncRNAs were evaluated to be genome-instability-associated from the high and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The reason for the high malignancy and drug resistance observed in glioma has been found to be that these tumors can effectively evade ferroptosis. Currently, many studies on glioma have focused on the relationship between lncRNAs and ferroptosis ( Deng, et al, 2020 ; Huang et al, 2021a ). The identification of FRLs is essential for finding potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the high malignancy and drug resistance observed in glioma has been found to be that these tumors can effectively evade ferroptosis. Currently, many studies on glioma have focused on the relationship between lncRNAs and ferroptosis ( Deng, et al, 2020 ; Huang et al, 2021a ). The identification of FRLs is essential for finding potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA can mediate gene regulation by interacting with DNA, RNA or protein, and its mechanism involves transcriptional regulation and post-transcriptional regulation that affect the activity of genes encoding proteins. It can directly combine with some proteins to form nucleic acid protein complexes, which plays a regulatory role by affecting the localization of proteins in cells, and it involves multiple pathways closely related to cancer development and progression, such as p53, NF-κB, PI3K/AKT and Notch ( Huang et al, 2021 ; Baumann, 2022 ; Reggiardo et al, 2022 ). Nevertheless, there are insufficient researches on the regulation of lipid metabolism by lncRNA in renal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that long non-coding RNAs (lncRNAs) are aberrantly expressed in various cancers and are involved in regulating genomic instability in cancer cells (12)(13)(14). LncRNAs are transcripts greater than 200 nt in length that do not encode proteins (15) and were considered to have no biological function (16).…”
Section: Introductionmentioning
confidence: 99%